Disciplines of higher education institutions that form valeological competence - Shevchenko, A. S.; Shevchenko, V. V. (My University, 2022)
Health saving issues are included in most state education standards of Ukraine. But for the full formation of valeological competence, special valeological disciplines are necessary ("Valeology", "Fundamentals of Life Safety", "Fundamentals of Medical Knowledge and Health Saving", "Health Pedagogy"). Related disciplines ("Ecology", "Occupational Safety") only partially form competence.
Keywords: valeological competence; health-saving competence; valeological disciplines; educational standards